Trade-Offs between Temperature and Fitness in Euschistus heros (Fabricius) (Hemiptera: Pentatomidae): Implications for Mass Rearing and Field Management - Barrufaldi, Ana Paula Frugeri [UNESP]; Hayashida, Rafael; Hoback, William Wyatt; Higley, Leon G.; Carvalho, Jose Romario de; Oliveira, Regiane Cristina de [UNESP] (MDPI, 2023)
The brown stink bug, Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae), is one of the most abundant soybean stink bug pests in Brazil. Temperature is a key factor that affects its development and reproduction, and fluctuating temperatures may impact the development and reproduction of E. heros differently from those under constant temperatures. The objective of this study was to evaluate the influence of constant and fluctuating temperature on the biological characteristics of E. heros in three successive generations. Treatments consisted of six constant temperatures (19 °C, 22 °C, 25 °C, 28 °C, 31 °C and 34 °C) and four fluctuating temperatures (25:21 °C, 28:24 °C, 31:27 °C, and 34:30 °C) evaluated for three successive generations. Second-stage nymphs were evaluated daily, and after they reached the adult stage, they were separated by sex, and the individual weight (mg) and pronotum size (mm) were recorded. After pair formation, eggs were collected to evaluate the pre-oviposition period, total number of eggs, and egg viability. The duration of the nymphal stage was reduced with an increase in both constant and fluctuating temperatures; however, at constant temperatures of 19 °C, 31 °C and 34 °C and fluctuating temperatures of 28:24 °C, there was no reproduction in adults. The base temperature and total degree day requirement for nymphal development were 15.5 °C and 197.4 dd, respectively. Pre-oviposition period (d), number of eggs per female, and viability of eggs (%) were affected by temperature across the generations. The multiple decrement life table analysis revealed that mortality was highest during the molting of the second-stage nymphs. These findings have important implications for E. heros’ laboratory mass-rearing programs and for its management in fields.
Keywords: brown stink bug; economic threshold; glycine max; life table multiple decrements